Bantengan Sebagai Identitas Budaya dan Sumber Pendapatan Alternatif Bagi Masyarakat Singosari - Anwar, Khoirul; Pujiono, Pujiono (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
This study examines the Bantengan performance in Singosari, Malang, positioned as both a vital cultural heritage and a strategic economic asset for the local community. The research explores how Bantengan serves as a cultural identity marker while functioning as an alternative income source that bolsters the creative economy and community-based tourism. Adopting a qualitative ethnographic economics approach, the study utilizes participant observation, in-depth interviews, and visual documentation involving art communities, MSME practitioners, traditional leaders, and local youth. The findings reveal that Bantengan operates through a dual function: primarily as a medium for preserving cultural values, social solidarity, and communal cooperation (gotong royong); and secondarily as an economic driver through the production of costumes, souvenirs, artistic training, and integration into the tourism sector. Despite its potential, the tradition faces significant hurdles, including limited resources and a lack of professional managerial training. The study concludes that Bantengan transcends its role as a symbolic cultural identity for the Singosari people, representing a strategic catalyst for inclusive, participatory, and sustainable local economic development.